2011
DOI: 10.1088/0268-1242/26/4/045012
|View full text |Cite
|
Sign up to set email alerts
|

Contactless electroreflectance, photoluminescence and time-resolved photoluminescence of GaInNAs quantum wells obtained by the MBE method with N-irradiation

Abstract: The optical properties of GaInNAs quantum wells (QW) grown by molecular beam epitaxy with and without N-irradiation (i.e. grown by the classical method) were investigated by the contactless electroreflectance (CER), temperature-dependent photoluminescence (PL) and time-resolved PL (TRPL). From CER measurements it was concluded that one type of nitrogen nearest-neighbor environment (In-rich environment) is dominant for GaInNAs QWs grown with N-irradiation whereas various nitrogen environments are present for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The presence of localized states also has a significant influence on the dynamics of PL at low temperature causing a longer PL decay time on the low-energy side than on the high-energy side [31,32]. An example of the temporal evolution of the PL spectrum (i.e., streak image) taken at 12 K for GaAs 0.944 Bi 0.056 MQWs is shown in figure 7 and the detailed analysis of PL decays at different energies is presented in figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of localized states also has a significant influence on the dynamics of PL at low temperature causing a longer PL decay time on the low-energy side than on the high-energy side [31,32]. An example of the temporal evolution of the PL spectrum (i.e., streak image) taken at 12 K for GaAs 0.944 Bi 0.056 MQWs is shown in figure 7 and the detailed analysis of PL decays at different energies is presented in figure 8.…”
Section: Resultsmentioning
confidence: 99%
“…Time-resolved photoluminescence (TRPL) using up-conversion technique [11] is commonly used for estimating carrier lifetimes of optoelectronic heterostructures and has been extensively used in connection with optimization of GaInNAs heterostructures [2,12-14]. However, most of the studies have been concerned with analyses of quantum wells [15]. Studies on GaInAsN epilayers have reported a wide variety of lifetimes in the range of 70 to 740 ps [8,16].…”
Section: Introductionmentioning
confidence: 99%
“…Absorption-like experiments such as electromodulated reflectance (ER) spectroscopy (i.e., photoreflectance, electroreflectance or contactless electroreflectance) together with photoluminescence (PL), which is an emission-like method, are applied to study the optical quality of QWs, [10][11][12] are used in this study. PL is sensitive to localized states, which are manifested mainly at low temperatures, and, therefore, the temperature-dependent PL measurements are performed in order to evaluate the scale of carrier localization in the investigated samples.…”
Section: Introductionmentioning
confidence: 99%